Childbirth in the Manawatu : women's perspectives : a thesis presented in fulfilment of the requirements for the degree of Master of Philosophy in Sociology at Massey University - McSherry, Margaret Anne (Massey University, 1986)
In most western countries the management of childbirth is surrounded by controversy and debate. New Zealand is no exception. Much of the debate centres round the role of medicine in the management of the healthy birth and the powerful influence exerted by the providers of maternity services over policy in this area. New Zealand research conducted on the management of childbirth, including consumer surveys, reflects the questions, methodologies and experience of the providers. Women's experiences of childbirth have not usually been considered legitimate data. This 'invisibility' of women in the research data has produced a body of knowledge about childbirth that is androcentric, reflecting male experience. Women, until recently, have been powerless to challenge this version of the reality of childbirth because they lacked access to medical knowledge and technology and because of the existence of an ideology of motherhood that imbued women with an expectation of self-sacrifice and nurturance impelling them to give priority to the perceived needs of the baby. The medical profession has been able to maintain control of the management of childbirth by requiring women's passivity and dependence 'for the sake of the baby'. In this way, medicine might, be said to act as an agent of social control of women, reproducing the unequal relations of gender by confirming women in their dependent roles of motherhood and domesticity. The pregnancy and birth experiences of 48 Manawatu women are explored in depth. The sample consisted of rural and urban women who, when pregnant, were expecting to have a normal labour and birth. Perinatal care was provided either by a specialist obstetric unit at the regional base hospital or by low technology, general practitioner (obstetric) units (GPU's) in the peripheral areas. Management of childbirth was found to be generally consistent with an obstetric or medical model of childbirth and similar in both high and low technology hospitals. Women's priorities for a quality service were more akin to a model of childbirth based on traditional midwifery. Women wanted a more 'holistic' form of maternity care; one that recognised and incorporated the socio-emotional dimensions of pregnancy and birth. Most women rejected the passive role expected of them in medical encounters and during the birth process. Women were likely to reject the association of childbirth with illness, preferring antenatal and perinatal services that were autonomous of general medical services. Few women, however, felt that the home could provide the ideal conditions for giving birth. The physical difficulty of labour and the level of medical intervention in the birth process were less likely to influence women's satisfaction with labour and birth that the quality of the emotional support women received from birth attendants and the level of the mothers' active participation in labour. Greater approval was found for the GPU as a place of birth, than for the specialist unit. Such findings challenge some of the current assumptions and directions of policy on maternity services in New Zealand.
Keywords: New Zealand -- Manawatu; Childbirth